After Lambana : myth and magic in Manila : a graphic novel - Victoria, Eliza, 1986- (Tuttle Publishing, 2022)
On the shadowy, noir-tinged streets of Manila, two friends seek a cure for a mysterious malady. To add to their problems, the Magic Prohibition Act has been adopted, and Lambana - the supernatural realm of the Diwata - has fallen. Slinky sirenas and wraith-like spirits populate this parallel universe of lurking danger and corruption. Will Lambana spill its secrets and provide the healing balm that's needed? Or will Conrad and Ignacio fail in their quest and perish in the process?